Customers' Reactions to Price Increases: Do Customer Satisfaction and the Perceived Motive Fairness Matter? - Homburg, Christian; Koschate, Nicole; Hoyer, Wayne D. (Journal of the Academy of Marketing Science, 2005)
Most of the previous research on price changes has focused on price decreases. This article investigates the effects of price increases at an individual level. The authors argue that customers' reactions to price increases (i.e., repurchase intentions) are strongly driven by two factors: the magnitude of the price increase and the perceived fairness of the motive for the price increase. In this context, the authors examine the role of customer satisfaction in influencing the impact of these two variables on repurchase intentions after a price increase. Their findings reveal that as satisfaction increases, the negative impact of the magnitude of a price increase is weakened. Furthermore, the results suggest that satisfaction moderates the impact of perceived motive fairness. The authors also find that the level of satisfaction can influence the valence of the perceived motives in response to a price increas
UnivIS-Import:2015-03-09:Pub.2005.rw.fbwiwi.migfk.custom
Keywords: Customer satisfaction; Experiment; Fairness; Price increases; Pricing